Anthocyanins from Hibiscus syriacus L. Inhibit Oxidative Stress-Mediated Apoptosis by Activating the Nrf2/HO-1 Signaling Pathway - Ilandarage Menu Neelaka Molagoda; Kyoung Tae Lee; Yung Hyun Choi; Gi-Young Kim (MDPI AG, 2020)
Hibiscus syriacus L. is distributed widely throughout Eastern and Southern Asia and considered as the national flower of South Korea. The extraction of several plant parts of H. syriacus L. is currently used as a natural remedy for several diseases, including breast and lung cancer, microbial infection, and chronic inflammation. However, the effect of the anthocyanin extract of H. syriacus L. petals (PS) in oxidative stress conditions has not been studied. In this study, we evaluated the cytoprotective effect of PS against H2O2-induced oxidative stress in HaCaT keratinocytes. In this study, we found that PS significantly inhibited H2O2-induced apoptosis of HaCaT keratinocytes. We also revealed that PS mediated-cytoprotective effect was associated with the increased expression of heme oxygenase-1 (HO-1) arising from the activation of nuclear factor erythroid 2-related factor-2 (Nrf2). PS also decreased H2O2-induced excessive intracellular ROS generation and restored H2O2-induced mitochondrial depolarization through the downregulation of mitochondrial ROS production. Furthermore, H2O2-induced Bax and caspase-3 expression was markedly abolished in the presence of PS. The inhibition of HO-1 by zinc protoporphyrin significantly attenuated the cytoprotective effect of PS in H2O2-treated HaCaT keratinocytes along with ROS generation, indicating that HO-1 crucially affects PS-mediated cytoprotective properties. Collectively, our results suggested that, under H2O2-mediated oxidative stress conditions, PS sustained a normal level of mitochondrial membrane potential and ROS generation in HaCaT keratinocytes by activating the Nrf2/HO-1 axis, exerting cytoprotective effects against oxidative stress.